Measurement of Prompt ? (2s) To J /? Yield Ratios in Pb-Pb and P - P Collisions at Snn =2.76 Tev - CMS Collaboration; Karapınar, Güler; Karapınar, Güler (American Physical Society, 2014)
The ratio between the prompt ψ(2S) and J/ψ yields, reconstructed via their decays into μ+μ-, is measured in Pb-Pb and p-p collisions at sNN=2.76 TeV. The analysis is based on Pb-Pb and p-p data samples collected by CMS at the Large Hadron Collider, corresponding to integrated luminosities of 150 μb-1 and 5.4 pb-1, respectively. The double ratio of measured yields (Nψ(2S)/NJ/ψ)Pb-Pb/(Nψ(2S)/NJ/ψ)p-p is computed in three Pb-Pb collision centrality bins and two kinematic ranges: one at midrapidity, |y|<1.6, covering the transverse momentum range 6.5<pT<30 GeV/c, and the other at forward rapidity, 1.6<|y|<2.4, extending to lower pT values, 3<pT<30 GeV/c. The centrality-integrated double ratio changes from 0.45±0.13(stat)±0.07(syst) in the first range to 1.67±0.34(stat)±0.27(syst) in the second. This difference is most pronounced in the most central collisions. © 2014 CERN. © 2014 CERN, for the The CMS Collaboration. Published by the American Physical Society under the terms of the »http://creativecommons.org/licenses/by/3.0/» Creative Commons Attribution 3.0 License. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.
Keywords: Tellurium compounds; Forward rapidity; Yield ratios; Kinematic range; Large Hadron Collider (LHC)